Use of nitrogen and PGPRs for management of spot blotch in barley (Hordeum vulgare) - AMIR, MOHAMMAD; SRIVASTAVA, J P; KHAN, ANAM; KUMAR, MANEESH; SINGH, RISHABH KUMAR; KHAN, F A (The Indian Journal of Agricultural Sciences, 2023)
Spot blotch disease of barley caused by Bipolaris sorokiniana is prevalent everywhere but causes significant yield losses under warm and humid climates. Use of fungicides is a common practice to control the spot blotch but at the same time it can pose a risk to environment as well as humans consuming such products. A field experiment was conducted to minimize the incidence of spot blotch in barley using different nitrogen levels and PGPRs as seed treatment. Application of lower nitrogen dose (50% of RDF – N1) and seed treatment with Azotobacter + PSB – B3) either individually or in combination significantly reduced the severity of spot blotch and increased the yield of barley. As such it may be concluded that spot blotch disease of barley can be managed by use of lower dose of nitrogen along with seed treatment with Azotobacter + PSB and use of fungicide may be avoided.